Effect of nitrogen and sulpbur application on grain and oil yields, nutrient uptake and protein content in transplanted gobhi sarson (Brassica napus subsp oleifera var annua) - Aulakh, M S; Pasricha, N S; Ahuja, K L (The Indian Journal of Agricultural Sciences, 2012)
A field study was conducted during winter season of 1988-89 and 1989-90 on NÂ· and SÂ·deficient Tolewal sandy-loam (Typical Ustisamments) soil, to investigate the effect of nitrogen and sulphur application on the transplanted gobhisarson (Brassica napus L. ssp oleifera DC. var annua L.). Pooled data of both the years showed that grain yield increased linearly from 0.85 tonne/ha in the control to 1.78 tonnes/ha on application of 100 kg N/ha. The maximum yield was obtained when N and S were applied together. Combined application of N and S significantly increased their concentration and uptake (kg/ha) in the grain, with positive and significant N x S interaction. Protein content in grain increased greatly from 12.7% in the control to 24.2% under N and S treatment. Application of 100 g N/ha + 20 kg S/ha increased. the oil yield to 999 kg/ha compared with 452 kg/ha in the control.